Reassessment of the Goiânia radioactive waste repository in Brazil using HYDRUS-1D - Pontedeiro, Elizabeth M.; Heilbron, Paulo F.; Perez-Guerrero, Jesus; Su, Jian; Van Genuchten, Martinus Th. [UNESP] (De Gruyter, 2018)
In September 1987 an accident occurred with a cesium chloride (CsCl) teletherapy source taken from a cancer therapy institute in Goiânia, Brazil. Misuse of the abandoned source caused widespread contamination of radioactive material (about 50 TBq of 137Cs) in the town of Goiânia. Decontamination of affected areas did lead to about 3,500 m3 of solid radioactive wastes, which were disposed in two near-surface repositories built in concrete in 1995. This paper documents a safety assessment of one of the low-level radioactive waste deposits containing 137Cs over a time period of 600 years. Using HYDRUS-1D, we first obtained estimates of water infiltrating through the soil cover on top of the repository into and through the waste and its concrete liners and the underlying vadose zone towards groundwater. Calculations accounted for local precipitation and evapotranspiration rates, including root water uptake by the grass cover, as well as for the effects of concrete degradation on the hydraulic properties of the concrete liners. We next simulated long-term water fluxes and 137Cs transport from the repository towards groundwater. Simulations accounted for the effects of 137Cs sorption and radioactive decay on radionuclide transport from the waste to groundwater, thus permitting an evaluation of potential consequences to the environment and long-term exposure to the public. Consistent with previous assessments, our calculations indicate that very little if any radioactive material will reach the water table during the lifespan of the repository, also when accounting for preferential flow through the waste.
Keywords: Cs-137 transport; Goiânia radioactive waste repository; HYDRUS-1D; Safety assessment